2016
DOI: 10.1182/blood.v128.22.640.640
|View full text |Cite
|
Sign up to set email alerts
|

CLL2-BIG - a Novel Treatment Regimen of Bendamustine Followed By GA101 and Ibrutinib Followed By Ibrutinib and GA101 Maintenance in Patients with Chronic Lymphocytic Leukemia (CLL): Results of a Phase II-Trial

Abstract: Introduction: In chronic lymphocytic leukemia (CLL), improved anti-CD20 antibodies such as obinutuzumab (GA101) and targeted drugs, such as ibrutinib, show very good efficacy and tolerability. With the CLL2-BIG trial, the German CLL Study Group designed a regimen composed of obinutuzumab and ibrutinib for induction and maintenance therapy. Patients with high tumor burden receive bendamustine as debulking resulting in the proposed "sequential triple-T" concept [Hallek M., Blood 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Infectious complications were reported in 92% (44/48) of trials with sufficient data for the final analysis. Table and Table summarize findings for those studies investigating ibrutinib as a single agent, or in combination with one or more other antineoplastics, respectively. One single‐agent trial and 3 combination studies included in the final infectious AE data had no reported infectious complications.…”
Section: Resultsmentioning
confidence: 99%
“…Infectious complications were reported in 92% (44/48) of trials with sufficient data for the final analysis. Table and Table summarize findings for those studies investigating ibrutinib as a single agent, or in combination with one or more other antineoplastics, respectively. One single‐agent trial and 3 combination studies included in the final infectious AE data had no reported infectious complications.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 41 patients who received debulking therapy, bendamustine appeared to reduce the risk of severe infusion-related reactions with obinutuzumab compared with no debulking (18 versus 48%, respectively) [53]. Of these 41 patients, 27 (66%) responded, with five patients (12%) achieving complete remission [54].…”
Section: Chemoimmunotherapymentioning
confidence: 98%
“…Overall response rates in the evaluable patients were 100% in both groups [71]. A further Phase 2 trial is ongoing in Germany (CLL2-BIG) which is studying the efficacy of sequential bendamustine as debulking agent in patients with high tumor burden followed by obinutuzumab-ibrutinib and ibrutinib-obinutuzumab maintenance therapy [54]. Promising interim data are available from 58 patients, which show a 100% ORR, half of them achieved a CR, and 47% a MRD negativity.…”
Section: Chemotherapy-free Regimensmentioning
confidence: 99%
“…Regular evaluations of the SAEs of all trials showed no unexpected or cumulative toxicities; in particular, no clinical and only few laboratory tumor lysis syndromes occurred with the CLL2-BAG regimen. Also, the bendamustine debulking appeared to reduce the risk of infusion-related reactions in the first induction cycle with obinutuzumab, as intended by the trial concept [61][62][63].…”
Section: Current Status Of the Bxx Trialsmentioning
confidence: 99%